Recapitulating the immune microenvironment in pediatric brain cancer: preclinical modeling strategies - Bhargav, Adip G.; Domino, Joseph S.; Akhavan, David; Goh, Jo Ling (Frontiers in Immunology, 2025)
Primary brain and CNS tumors comprise the most common tumors in children and are the most common cause of cancer deaths in this population. Pediatric primary malignant brain tumors including high-grade glioma and medulloblastoma account for a significant proportion of these cancer deaths. Advances in the surgical management and adjuvant treatment paradigms have improved the prognosis of many patients with these tumors, but there remains a subset of treatment-resistant tumors or tumors with unique genetics aberrations and aggressive phenotypes that confer a poor prognosis. Immunotherapeutic strategies have demonstrated promise in pre-clinical studies and early clinical trials. However, high-fidelity evaluation of these novel therapeutics and subsequent clinical translation has faced challenges due to the limitations of conventional preclinical models that have been used to study the pathophysiology and treatment response of these tumors. Recent efforts have been directed towards more accurate modeling of the molecular and histological heterogeneity observed in these tumors as well as creating immunocompetent animal models that resemble the tumor immune milieu. In this review, we provide an overview of contemporary and emerging preclinical modeling strategies with a focus on those that strive to recapitulate the immune and microenvironment features of malignant pediatric brain tumors.